Clinical studies with drugs and biologics aimed at slowing or reversing normal aging processes—emerging results and future perspectives - Ricardo P. Garay (Exploration of Drug Science)
Five families of investigational products are in clinical investigation to slow or reverse normal aging processes [longevity candidates, mesenchymal stem cells, senolytics drugs, sirtuin activators, and nicotinamide adenine dinucleotide (NAD)+ precursors]. The longevity candidates, vitamin D and metformin, appear to significantly reduce all-cause mortality and prolong life expectancy. This should be confirmed by interventional studies. The mesenchymal stem cell family is the most advanced in clinical trial development [phase 2b randomized controlled trial (RCT)]. An allogeneic bone marrow stem cell preparation (Lomecel-B) reduced locomotor frailty in older people. The improvement in locomotion was modest. In the future, attempts could be made to improve potency through a precondition or genetic modification of naive bone marrow stem cells. Autologous adipose stem cell-assisted fat grafting increased graft survival, facial volume, and skin quality. The association of the senolytic drugs dasatinib and quercetin was well tolerated, with low brain penetration of dasatinib and undetectable levels of quercetin. The sirtuin-1 activator resveratrol (combined with physical exercise) improved physical function in older adults with physical limitations. The NAD+ precursor nicotinamide riboside improved physical exercise performance. In conclusion, Lomecel-B is the most advanced agent in clinical trial development for normal aging processes (phase 2b for locomotion frailty), followed by resveratrol and nicotinamide riboside.